2016
DOI: 10.12968/jowc.2016.25.5.242
|View full text |Cite
|
Sign up to set email alerts
|

A review of the evidence for adjustable compression wrap devices

Abstract: Compression therapy is a key component in the effective management of people with lower limb problems associated with venous, lymphatic and fat disorders such as lipoedema. Individuals with lymphoedema, venous ulceration and lipoedema often require long-term compression therapy to prevent and manage problems such as chronic ulceration and skin changes, persistent swelling and shape distortion. Challenges remain in achieving acceptable, safe, effective and cost-efficient compression therapy choices. Adjustable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 19 publications
(40 reference statements)
1
23
0
1
Order By: Relevance
“…However, there is clinical evidence that compression wrap devices improve the quality of life and independence of patients. 12 Although infection is a significant risk factor for lymphedema, 13 patients in this study reported low rates of postoperative infection and erysipelas, probably due to the small sample size. Radiation therapy is also a risk factor, as it promotes the formation of tissue fibrosis, with consequent lymphatic vasoconstriction, significant damage to the lymph node filtration function and altered immune response.…”
mentioning
confidence: 65%
“…However, there is clinical evidence that compression wrap devices improve the quality of life and independence of patients. 12 Although infection is a significant risk factor for lymphedema, 13 patients in this study reported low rates of postoperative infection and erysipelas, probably due to the small sample size. Radiation therapy is also a risk factor, as it promotes the formation of tissue fibrosis, with consequent lymphatic vasoconstriction, significant damage to the lymph node filtration function and altered immune response.…”
mentioning
confidence: 65%
“…Studies regarding the evaluation of dynamic performance of AW with regards to the dosage are limited and consist largely of case studies using a single type of AW. 51 Published studies focus on investigation of a singular product line and consequently the results cannot be taken to represent an entire product line or AW as a compression category CLINICAL PEARL In order to maintain medically efficacious dosages, it is very important to replace garments every six months Similar to MCS, AW manufactures have developed light and firm, ready-to-wear (RTW) and custom products. We found no studies comparing the dynamic performance of different textiles used to construct the AW, such as light versions compared with classic styles.…”
Section: Adjustable Wrap Compression Dosagementioning
confidence: 99%
“…Although compression therapy is the mainstay of treatment (Lymphoedema Framework, 2012), many studies do not focus on this treatment modality alone, failing to mirror study designs when conducting research, which impacts on the validity of research outcomes (Thomas, 2014). A recent review, conducted by Williams (2016), of evidence available to underpin the use of adjustable velcro compression wraps, using the databases including Medline, CINAHL and the Cochrane library, among others, concluded that most of the evidence is descriptive and that there is a lack of robust evaluation in terms of the economic value and in the long-term management of chronic diseases. This is further highlighted in the literature review conducted by Thomas (2017).…”
Section: Psychological Supportmentioning
confidence: 99%
“…The easywrap lower limb section Lee (2014), advantages of using velcro wrapping systems include being less bulky than bandages. Williams (2016) states they are suitable for self-application, easier to apply where patients have problems with garment application, and are a less time consuming, safer option for treatment.…”
Section: Patient Educationmentioning
confidence: 99%